Educação sexual na escola : sentidos subjetivos do sujeito que aprende em uma escola pública de Rio Branco - Acre - Miranda, Pedro Raimundo Mathias de (2018)
Intentional Sex Education (SE) at school contributes to amplify the civic formation of students, preparing them for a more humanized living in society. However, few schools have committed themselves to systematically offer pedagogical activities of SE, as advocated by documents that consider education in sexuality as part of Human Rights and Sexual and Reproductive Rights, over the complexity of implementing such activities. Nowadays, the inclusion of intentional SE at school is a social necessity, due to, among other matters, unwanted teenage pregnancy. Considering the total number of babies born alive to mothers under the age of 19, in 2015, the state of Acre registered the highest percentual (27%) in all the Brazilian territory (an average of 18,1%). The present research, of qualitative approach, inspired by the Subjectivity Theory and the Qualitative Epistemology by Gonzalez Rey, investigates how High School students’ subjective senses about sexuality configure themselves and how such sense configurations transform, through dialog and problematization-oriented educational practices, under a perspective of emancipatory approach to Sex Education. 22 encounters were held with 17 students from a public school from Rio Branco, Acre, to dialog about several topics related to sexuality, utilizing varying teaching resources. The production of data occurred during the execution of the activities through group and individual conversations, completing sentences, drawings, essays and individual records on a notebook reserved for this purpose. The constructive-interpretative analysis of the data included the elaboration of indicators and hypotheses for the construction of the theoretical model about the object of study. The results indicate that the execution of dialog-oriented practices favors the production of subjective senses related to the sexuality of the research participants as far as the expression and experience of sexuality. The discussions about relationships, media and sexuality, sexual and reproductive functions of the genital system, conception and unwanted pregnancy prevention, Sexual and Reproductive Rights, sexual discrimination and prejudice at school, contributed to the autonomy, well-being and respect from the research participants towards the different manifestations of sexuality. The results confirm the thesis that intentional sex education at school, based on an emancipatory approach, through dialog and problematization-oriented practices, creates suitable conditions to produce subjective senses adequate to the full-fledged, responsible and pleasurable experience of sexuality. The results also offer subsidies to (re)think about means to promote intentional sex education of teenagers at school, under a perspective of emancipatory approach.